2001
DOI: 10.1128/jb.183.16.4702-4708.2001
|View full text |Cite
|
Sign up to set email alerts
|

Treponema pallidum 3-Phosphoglycerate Mutase Is a Heat-Labile Enzyme That May Limit the Maximum Growth Temperature for the Spirochete

Abstract: In the causative agent of syphilis, Treponema pallidum, the gene encoding 3-phosphoglycerate mutase, gpm, is part of a six-gene operon (tro operon) that is regulated by the Mn-dependent repressor TroR. Since substrate-level phosphorylation via the Embden-Meyerhof pathway is the principal way to generate ATP in T. pallidum and Gpm is a key enzyme in this pathway, Mn could exert a regulatory effect on central metabolism in this bacterium. To study this, T. pallidum gpm was cloned, Gpm was purified from Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Gherardini and co-workers (16,20) further suggested that TroRmediated repression of Gpm within the central nervous system would decrease treponemal metabolism and thereby contribute to the latency of syphilitic infection. Because T. pallidum can only generate ATP by glycolysis, such a genetic arrangement seems inherently problematic because TroR-mediated repression of Gpm would hinder generation of ATP and thus the ability of the bacterium to escape a potentially metal-toxic environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gherardini and co-workers (16,20) further suggested that TroRmediated repression of Gpm within the central nervous system would decrease treponemal metabolism and thereby contribute to the latency of syphilitic infection. Because T. pallidum can only generate ATP by glycolysis, such a genetic arrangement seems inherently problematic because TroR-mediated repression of Gpm would hinder generation of ATP and thus the ability of the bacterium to escape a potentially metal-toxic environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to encoding an ATPase (TroB), two cytoplasmic membrane permeases (TroC and TroD), and a DtxR-like metalloregulator (TroR), the operon also encodes the glycolytic enzyme phosphoglyceromutase (Gpm) (13). Because the T. pallidum Gpm has no requirement for metals (16), the physiological benefit of transcriptionally linking the spirochete's sole copy of this essential enzyme to the Tro transporter genes is unclear.…”
mentioning
confidence: 99%
“…The protein TroR [22][23][24][25][26] in this study is from Treponema pallidum, a sexually transmitted human pathogen that usually disseminates from the genital area to diverse organs. The understanding of T. pallidum's biology and physiology remains limited largely because of the inability to culture it in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The typical heat shock response regulated by 32 is lacking (105,296), possibly reflecting the sensitivity of the organism to growth temperature (95). At least one T. pallidum enzyme is unstable at normal body temperature (22), suggesting that the heat lability of enzymes may also contribute to the slow growth of the organism. Heat therapy for late neurosyphilis was introduced in 1918 by the Viennese psychiatrist Julius Wagner von Jauregg (326), a discovery for which he later won the Nobel Prize in Medicine.…”
Section: In Vivo and In Vitro Growth Of T Pallidummentioning
confidence: 99%